2011
DOI: 10.1088/0031-9155/56/18/019
|View full text |Cite
|
Sign up to set email alerts
|

Investigating potential physicochemical errors in polymer gel dosimeters

Abstract: Measurement errors in polymer gel dosimetry can originate either during irradiation or scanning. One concern related to the exothermic nature of polymerization reaction was that the heat released in polymer gel dosimeters during irradiation modifies their dose response. In this paper, the effect of heat released from the exothermal polymerization reaction on the dose response of a number of dosimeters was studied. In addition, we investigated whether heat-generated geometric distortion existed in newly propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…In the past, several authors have found discrepancies between the gel measured dose and the TPS calculated dose values which are not attributed to TPS related errors (Low et al 1999, Cosgrove et al 2000, Cardenas et al 2002, Watanabe et al 2005, Crescenti et al 2007. These discrepancies were attributed to volumetric effects (MacDougall et al 2008, Dumas et al 2006, Xu et al 2010, De Deene et al 2002b, Vergote et al 2004, cooling history (De Deene et al 2007), temperature during irradiation (Salomons et al 2002, Sedaghat et al 2010, 2011b, oxygen contamination effects (Hepworth et al 1999, Sedaghat et al 2011a and imaging artefacts (De Deene et al 2000a, 2000b, De Deene and De Wagter 2001.…”
Section: Introductionmentioning
confidence: 99%
“…In the past, several authors have found discrepancies between the gel measured dose and the TPS calculated dose values which are not attributed to TPS related errors (Low et al 1999, Cosgrove et al 2000, Cardenas et al 2002, Watanabe et al 2005, Crescenti et al 2007. These discrepancies were attributed to volumetric effects (MacDougall et al 2008, Dumas et al 2006, Xu et al 2010, De Deene et al 2002b, Vergote et al 2004, cooling history (De Deene et al 2007), temperature during irradiation (Salomons et al 2002, Sedaghat et al 2010, 2011b, oxygen contamination effects (Hepworth et al 1999, Sedaghat et al 2011a and imaging artefacts (De Deene et al 2000a, 2000b, De Deene and De Wagter 2001.…”
Section: Introductionmentioning
confidence: 99%
“…To elucidate the origins of these dose discrepancies caused by the calibration using small calibration phantoms, several experiments were set up to investigate possible physico-chemical effects that may influence the accuracy of polymer gel dosimetry. Several hypotheses were already proposed in the scientific literature for these differences (MacDougall et al 2008, Dumas et al 2006, Xu et al 2010, De Deene et al 2007, Salomons et al 2002, Sedaghat et al 2010, Hepworth et al 1999, Sedaghat et al 2011a, 2011b. These hypotheses included the effect of inhomogeneous distribution of oxygen before irradiation (Sedaghat et al 2011a(Sedaghat et al , 2011b and temperature effects before and during irradiation (Cosgrove et al 2000, Salomons et al 2002, De Deene et al 2006, 2007, Sedaghat et al 2010.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is a mistake to assume that normoxic gel dosimeters are completely insensitive to oxygen. Normoxic gel dosimeters still require casting materials that avoid infiltration of ‘fresh’ oxygen [ 259 , 260 ]. Large amounts of oxygen in the gel dosimeter results in inhibition of the polymerization reaction, while small amounts result in a promotion of polymerization.…”
Section: Polymer Gel Dosimetersmentioning
confidence: 99%